2004
DOI: 10.21273/hortsci.39.7.1740
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Water Requirements of Four Turfgrasses in the Transition Zone

Abstract: Water requirements for `Meyer' zoysiagrass (Zoysia japonica Steud., hereafter referred to as zoysia), `Midlawn' bermudagrass [Cynodon dactylon (L.) Pers. × C. transvaalensis Burtt-Davy, hereafter referred to as bermuda], `Falcon II' tall fescue (Festuca arundinacea Schreb.) and `Brilliant' kentucky bluegrass (Poa pratensis L., hereafter referred to as bluegrass) were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
101
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 14 publications
(29 reference statements)
9
101
0
2
Order By: Relevance
“…Water requirements for turfgrass growth have been based on water use rates and quantified through measurement of evapotranspiration rate (ET). Water requirements vary with turfgrass species (Youngner et al, 1981; Aronson et al, 1987; Kim and Beard, 1988; Fry and Butler, 1989; Fu et al, 2004) and within cultivars of the same species (Shearman, 1986; Kopec et al, 1988; Shearman, 1989; Bowman and Macaulay, 1991; Salaiz et al, 1991; Ebdon and Petrovic, 1998). Water use rate is also affected by environmental factors, such as the availability of soil moisture.…”
mentioning
confidence: 99%
“…Water requirements for turfgrass growth have been based on water use rates and quantified through measurement of evapotranspiration rate (ET). Water requirements vary with turfgrass species (Youngner et al, 1981; Aronson et al, 1987; Kim and Beard, 1988; Fry and Butler, 1989; Fu et al, 2004) and within cultivars of the same species (Shearman, 1986; Kopec et al, 1988; Shearman, 1989; Bowman and Macaulay, 1991; Salaiz et al, 1991; Ebdon and Petrovic, 1998). Water use rate is also affected by environmental factors, such as the availability of soil moisture.…”
mentioning
confidence: 99%
“…However, bermudagrass had significantly less root uptake, and measured 29% of 14 C applied. Physiologically, cool‐season grasses have greater water requirements than warm‐season grasses . These differences are likely associated with more root absorption of soil‐applied herbicides for cool‐season grasses compared with bermudagrass.…”
Section: Resultsmentioning
confidence: 55%
“…The spotting solution had a nonionic surfactant (Activator 90 ® ; Loveland Industries, Greeley, CO) included at 0.125% v/v to aid deposition of droplets on leaves. This methodology is similar to previous research for treating turfgrasses with radiolabeled herbicides …”
Section: Methodsmentioning
confidence: 79%
“…Fu et al . () reported that tall fescue, bermudagrass and Japanese lawngrass ( Zoysia japonica Steud.) displayed the same level of turf quality as well‐watered turfgrass when irrigated at 60 or 80% of evapotranspiration.…”
Section: Introductionmentioning
confidence: 99%